Analysis of the interaction of adhesives containing functional resin monomers to irradiated and artificially eroded human dentin - Costa, Mylena Proença (2023)
With the knowledge regarding the disbiose related to caries and habit changes, other clinical dentin conditions have been evidenced, emerging new challenges on preventive and therapeutic approaches. Particular clinical events as irradiated caries and tooth wear, modulated by erosion, are becoming more frequent. The resulting dental substrates present significant compositional and structural alterations, which encounter challenges on the bonding process. These characteristics must be elucidated to allow effective approaches. The development of self-etching and universal systems containing functional monomers, in particular the 10-MDP (10-methacryloyloxydecyl dihydrogen phosphate), introduced a new promising category of dentin bonding system (DBS) due to its capacity to associate micromechanical adhesion with the chemical interaction with dental structure. These properties confer short time-consuming, less technical and postoperative sensitivity. Since then, other systems containing functional monomers have been launched in the market as the carboxylic and phosphonic monomers. Additionally, bioactive components based on Giomer technology that contain surface pre-reacted glass particles (S-PRG) pre-treated with polyacrylic acid have been revolutioning these systems. These properties however, calls for scientific evidences, in particular to the comprehension regarding this mechanism associated with altered substrates. The aim of this study was to evaluate the interaction of main self-etching and universal dentin bonding systems based on distinct functional monomers concerning bonding properties, when applied on sound, irradiated and artificially eroded dentin. The tested DBSs were: Adper Scotchbond Multipurpose (MP), Clearfil SE Bond (SE), FL Bond II (FL), Adper Single Bond Universal (SU) and BeautiBond Xtreme (BX). They were tested by means of bond strength to dentin (BS) by microtensile test after 6 months, supplemented by analysis of the mode of fracture using optical microscopy (40x); qualitative analysis by Scanning Electron Microscopy (SEM); degree of conversion (DC) using Fourier Transform Infrared Spectroscopy (FTIR) and wettability (W) of the surface before and after the application of the DBSs. Results showed normal and homogeneous distribution and were analyzed trough ANOVA and Tukey tests (p<0.05). 10-MDP-based DBSs showed higher BS values, while those containing carboxylic and phosphonic monomers were the most stable. Altered substrates were significant in BS reduction for all cases. Regardless the monomeric composition, universal DBSs showed higher GC values. In the W analysis, altered substrates also negatively affected the performance. FL was the most hydrophobic among DBSs suggesting the bioactive ingredient influence on the dispersion of the adhesive. It can be concluded that DBSs containing functional monomers were impaired when applied to altered substrates, indicating that the restructuring and composition of the dentin affect the chemical relation of its interaction. The incorporation of a bioactive component does not seem to affect FL functionality in general terms.